Pola Adopsi Pengelolaan Ramah Lingkungan Untuk Konservasi Rawa Pening di Desa Asinan - Supriyanto, Sapto; Listyorini, Haniek (Program Studi Pendidikan Kependudukan dan Lingkungan Hidup, 2025)
This study aims to identify green management adoption patterns by local communities in Asinan Village for Rawa Pening conservation, analyze influencing factors, evaluate impacts on environmental conservation and socio-economic conditions, and formulate effective adoption models. The research employed a mixed-method approach through in-depth interviews with 20 key informants, focus group discussions, participatory observation, surveys of 100 respondents, and document studies. Results revealed four adoption stages: awareness (85%), interest (68%), evaluation (45%), and trial/adoption (32%). Five significant factors influencing adoption were education level (β = 0.285), information access (β = 0.312), community social capital (β = 0.267), institutional support (β = 0.245), and perceived economic benefits (β = 0.198). Adoption demonstrated positive environmental impacts with 15% COD reduction, 12% BOD reduction, and 25% income increase for organic farmers. The developed Integrated Green Management Adoption Model incorporates four main components: community capacity building, information and communication system development, local institutional strengthening, and sustainable incentive systems.